Observation of the Relationship between Ocean Bathymetry and Acoustic Bearing-Time Record Patterns Acquired during a Reverberation Experiment in the Southwestern Continental Margin of the Ulleung Basin, Korea - Youngcheol Jung (MDPI AG, 2021)
We observed a distinct drop-off region in the bearing-time record of acoustic reverberation data acquired from the south-western continental margin of the Ulleung Basin, East Sea, in the summer of 2015. 3 kHz continuous waves with pulse lengths of 0.1, 0.3, and 1.0 s were used as source pulses, with an R/V Cheonghae vessel towing a variable depth source and a triplet towed array toward the deep sea from shallow water. The observed pattern changed as the R/V Cheonghae moved across the continental slope further into the sea. This pattern arises as a result of the downward-refracted beams in the 1/2 convergence zone interacting with the soft bottom. In addition, the boundary of the drop-off region was modeled with the two-way maximum travel time of the first bottom-reflected rays using the bathymetry model of the General Bathymetric Chart of the Oceans, 2020. Some discrepancies were observed when comparing the modeled curve to the measured results, and the inaccuracy of the bathymetry model on the continental slope could be the main cause of these discrepancies. This pattern could be useful for bathymetry mapping, as well as estimations of source and receiver configurations.